Czytanie literatury - Węgrzyniak, Anna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The article aims to persuade readers of an idea based on the notion that the act of reading can be and is heavily influenced by methods, habits, socio-economic status, the fact whether it is done privately or in the open. On the one hand, there is a professional reader — student, teacher, writer. On the other, there is reading privately for pleasure. My interest and area of expertise — so to speak — is mostly the effect the act of reading has on "a private reader", such as the dark side of identity issues, existential problems.